Analisis Kecurangan Akademik Mahasiswa dalam Kajian Teori Fraud Hexagon - Sevira Ananditya; Ratieh Widhiastuti (Universitas Muhammadiyah Magelang, 2026)
This study aims to examine the influence of the fraud hexagon on academic fraud among students in the Faculty of Economics and Business at Universitas Negeri Semarang, Class of 2024. This study employs a quantitative method using a questionnaire in the form of a Google Form distributed via personal and group chats. The sampling technique selected was proportional random sampling to ensure that each department was proportionally represented, resulting in a sample of 322 students. Instrument validation was conducted using validity and reliability tests to ensure the quality of the indicators used. Data analysis was performed using descriptive statistical analysis and Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of the study indicate that the variables of pressure, rationalization, and arrogance do not influence student academic fraud, while the variables of opportunity, ability, and collusion do influence student academic fraud. The recommendation from this study is that the university should strengthen its monitoring system and minimize opportunities for academic fraud, as well as channel students’ potential toward more positive directions to curb academic fraud.